Savage or civilised? : manners in colonial Australia - Russell, Penelope Ann. (Sydney : New South, 2010)
In colonial Australia manners marked the difference between savagery and civilisation, between vulgarity and refinement. Colonists recoiled in shock and confusion at the customs of Indigenous Australians, but they also sensed the savagery lurking in white society. Manners mattered, to individuals and to society.
Includes bibliographical references (p. 363-401) and index.
Keywords: Etiquette -- Australia -- History -- 1788-1900.; Courtesy -- Australia -- History -- 1788-1900.; Cultural protocols; Worimi / Gadang / Kattang people (E2) (NSW SI56-02); Settlement and contacts - Settlers; Settlement and contacts - Colonisation - 1788-1850.; Australia -- Social life and customs -- 1788-1900.; Australia -- History -- 1788-1900.; Glenormiston (W Vic SJ54-12); Karuah River (NSW N Coast SI56-02)